The ecology of coexistence and conflict in Cyprus : exploring the religion, nature, and culture of a Mediterranean island - Dietzel, Irene, 1979- (Berlin/Boston : De Gruyter, 2014)
What is the significance of sustainable resource management for the functioning of Mediterranean island societies? How do human-environment relations reflect in a multi-ethnic religious landscape? This book poses these questions in the context of the Ottoman, British, and modern history of Cyprus. It explores the socio-ecological dimension of the Cyprus Conflict and considers the role of local environmental practices for historical coexistence and modern division. The book synthesizes theoretical approaches from the research on 'religion and ecology' with the anthropology of Cyprus, with the goal to develop and establish an ecological perspective on coexistence and conflict in the Mediterranean.
Frontmatter -- Acknowledgements -- Contents -- 1. Introduction -- 2. Chapter 1: Nature, culture and religion in theory: an exploration of ideas -- 3. Chapter 2: Nature, culture and religion in Mediterranean context -- 4. Chapter 3: Environmental ethics and eco-theology: a discourse on values -- 5. Chapter 4: Cyprus in the Ottoman Mediterranean: a historical introduction to Part II -- 6. Chapter 5: The ecology of coexistence -- 7. Chapter 6: Religion and ecology in pre-modern Cyprus -- 8. Chapter 7: From colonial rule to modern division: a historical introduction to Part III -- 9. Chapter 8: the ecology of conflict -- 10. Chapter 9: Nature conservation and sustainability in conflict discourse -- 11. Conclusion -- 12. Appendix -- 13. Bibliography -- Subject Index.
Online resource; title from PDF title page (EBSCO, viewed July 31, 2015).
Includes bibliographical references and index.
In English.
Master record variable field(s) change: 650, 651
Keywords: Cyprus -- Religion; Cyprus -- History; Nature -- Religious aspects; Ecotheology -- Cyprus; HISTORY -- Middle East -- General; Ecotheology; Nature -- Religious aspects; Religion; Cyprus; Cyprus -- Religion; Cyprus -- History; Ecotheology -- Cyprus; HISTORY -- Middle East -- General; Nature -- Religious aspects; Religion, Jewish Studies, Theology; Religion; Geschichte Asiens; Electronic books; History; Electronic books